EVOLUTION OF THE ANTIOXIDANT CAPACITY OF FRANKFURTER SAUSAGE MODEL SYSTEMS WITH ADDED CHERRY EXTRACT (Prunus avium L.) DURING REFRIGERATED STORAGE - ISAZA M., Yeni L.; RESTREPO M., Diego A.; LÓPEZ V., Jairo H.; OCHOA G., Oscar A.; CABRERA T., Kenneth R. (Vitae, 2011)
The aim of this work was to establish the antioxidant capacity evolution in a model system of Frankfurter type sausages with added cherry extract through the Folin Ciocalteu, pH differential, FRAP, ABTS, and DPPH methods. Therefore, the total phenol and total anthocyanin contents, the reducing power, and the radical scavenger activity were monitored during a two-month period of storage time in refrigerated conditions (4 ± 1°C). A factorial experimental design was applied with two factors (cherry extract and storage time), and comparative evaluations were made with respect to a product similarly formulated and elaborated without cherry extract but with added sodium ascorbate (0.05%). Results showed no significant difference (p > 0.05) with respect to the total anthocyanin content for any sausage with added cherry extract; while total phenols, reducing capacity and radical captive activity were significantly higher (p < 0.05) in sausages with cherry extract (for the three doses) than in the case of the sausages with no added cherry extract. Moreover, storage time was significant for all cases, because there was a decrease in all the studied variables related to it.